Laboratory Evaluation and Clinical Characteristics of 2,132 Consecutive Unselected Patients with Venous Thromboembolism – Results of the Spanish Multicentric Study on Thrombophilia (EMET*-Study) - Mateo, José; Oliver, Artur; Borrell, Montserrat; Sala, Núria; EMET Group; Fontcuberta, Jordi (Thrombosis and Haemostasis, 1997)
Previous studies on the prevalence of biological abnormalities causing venous thrombosis and the clinical characteristics of thrombotic patients are conflicting. We conducted a prospective study on 2,132 consecutive evaluable patients with venous thromboembolism to determine the prevalence of biological causes. Antithrombin, protein C, protein S, plasminogen and heparin cofactor-II deficiencies, dysfibrinoge-nemia, lupus anticoagulant and antiphospholipid antibodies were investigated. The risk of any of these alterations in patients with familial, recurrent, spontaneous or juvenile venous thrombosis was assessed. The overall prevalence of protein deficiencies was 12.85% (274/2,132) and antiphospholipid antibodies were found in 4.08% (87/2,132). Ten patients (0.47%) had antithrombin deficiency, 68 (3.19%) protein C deficiency, 155 (7.27%) protein S deficiency, 16 (0.75%) plasminogen deficiency, 8 (0.38%) heparin cofactor-II deficiency and 1 had dysfib-rinogenemia. Combined deficiencies were found in 16 cases (0.75%). A protein deficiency was found in 69 of 303 (22.8%) patients with a family history of thrombosis and in 205/1,829 (11.2%) without a history (crude odds ratio 2.34, 95% Cl 1.72-3.17); in 119/665 (17.9%) patients with thrombosis before the age of 45 and in 153/1,425 (10.7%) after the age of 45 (crude odds ratio 1.81, 95% Cl 1.40-2.35); in 103/616 (16.7%) with spontaneous thrombosis and in 171/1,516 (11.3%) with secondary thrombosis (crude odds ratio 1.58, 95% Cl 1.21-2.06); in 68/358 (19.0%) with recurrent thrombosis and in 206/1,774 (11.6%) with a single episode (crude odds ratio 1.78,95% Cl 1.32-2.41). Patients with combined clinical factors had a higher risk of carrying some deficiency. Biological causes of venous thrombosis can be identified in 16.93% of unselected patients. Family history of thrombosis, juvenile, spontaneous and recurrent thrombosis are the main clinical factors which enhance the risk of a deficiency. Laboratory evaluation of thrombotic patients is advisable, especially if some of these clinical factors are present.